Transitions in Care from the Hospital to Home for Patients With Diabetes - Hirschman, Karen B. (Diabetes Spectr, 2014)
In Brief Diabetes is a common coexisting chronic condition among older adults that can complicate a hospitalization and transition back to the community. The Transitional Care Model, which offers a set of time-limited, hospital-to-home services coordinated by a master's-prepared advanced practice nurse, is one option that could improve outcomes for patients with diabetes. A descriptive case study is presented.